Opening markets for trade in services : countries and sectors in bilateral and WTO negotiations / edited by Juan A. Marchetti and Martin Roy. - Marchetti, Juan A.; Martin, Roy (Cambridge University Press, 2008)
Trade in services is an increasingly important part of global trade and, as such, figures prominently in multilateral, regional and bilateral trade negotiations. In this volume of essays, academics, negotiators and experts from various international organizations explore the achievements of such negotiations, together with the challenges and opportunities which arise and the motivations that come into play in such negotiations. The contributions highlight issues in important services sectors, such as distribution, energy, finance, telecommunications, air transport and the postal and audiovisual sectors, as well as areas such as cross-border trade and government procurement. Case studies look into the experiences of specific countries. The focus on sector analysis and country experiences sheds light on the state of services liberalization and the regulation of international trade in services at the beginning of the twenty-first century, making this an indispensable guide to ongoing and future international negotiations on this topic.